Strengthening Micro and Small Business Capacity through Digital Marketing to Increase MSME Income in Semper Barat, North Jakarta - Achmad Tarmizi; Dian Meliantari; Agung Suprayitno (Golden Ratio of Community Services and Dedication, 2026)
This community service program aims to strengthen the marketing capacity of micro and small business actors in RT 008/010, Semper Barat, North Jakarta through digital marketing-based empowerment. Preliminary assessment revealed that most MSME actors relied on conventional marketing methods and possessed limited digital literacy, which constrained their ability to expand market reach and improve sales performance. The program was implemented using a participatory capacity-building approach that integrated digital marketing training, basic branding and content creation, and hands-on mentoring in the use of social media and online business platforms. Program outcomes were evaluated through pre- and post-training assessments, observation of changes in promotional practices, and short-term monitoring of early market responses. The results indicate improvements in participants’ digital literacy, promotional skills, and initial engagement with online marketing channels. Although early economic impacts were modest, the observed behavioral changes provide a foundation for longer-term business development. These findings suggest that community-based digital marketing empowerment can contribute to strengthening MSME competitiveness and supporting local economic resilience in urban communities.